Controlling Cholesterol the Natural Way : Eat Your Way to Better Health with New Breakthrough Food Discoveries - Cooper, Kenneth H. (New York Bantam Books, 1999)
All New Plan to Lower Cholesterol without Drugs.
Include Glossary and Index.
Keywords: Low-cholesterol diet -- Exercise therapy -- Functional foods